Successful management of coagulation dysfunction in a patient with fulminant myocarditis: a case report - Dong, Shanshan; Peng, Qi; Lu, Kai; Wei, Qimei; Yang, Jun (Frontiers in Cardiovascular Medicine, 2025)
Fulminant myocarditis (FM) is an acute, diffuse inflammatory myocardial disease characterized by abrupt onset and extremely rapid progression. Patients typically exhibit haemodynamic abnormalities that may lead to respiratory failure, liver and renal failure, and subsequent coagulopathy. Collectively, these complications significantly increase the risk of early mortality. Currently, there is limited research on coagulation dysfunction associated with FM; therefore, achieving a rebalancing of the coagulation system is a challenge for successful treatment. We report a case of coagulation disorder secondary to FM, in which the patient recovered successfully and was discharged following comprehensive treatment and correction of coagulation function. By analyzing the etiology of this condition and emphasizing strategies for correcting coagulation disorders, we aim to provide valuable references for clinical diagnosis and management.